Kebangkitan Pekerjaan Platform dalam Industri Komunikasi di Indonesia: Memahami Ekosistemnya - Algooth Putranto; Celixa Amenity Yovanka; Arsa Widitiarsa Utoyo (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
The COVID-19 pandemic accelerated the shift to remote and flexible work globally, prompting a rise in platform work, especially within the Indonesian communication industry. As platform work becomes more integral to the digital economy, understanding its ecosystem is crucial to ensure sustainable opportunities for freelancers and meet industry demands. This study aims to analyze the growth of platform work in Indonesia's communication sector, focusing on freelancers who utilize digital platforms. Using a qualitative approach, the study combines a literature review with snowball sampling, gathering insights from 10 participants involved in communication-focused freelance work. Primary data were derived from official publications, complemented by secondary data from participant interviews to identify challenges and opportunities within platform work ecosystems. Findings indicate that platform work has democratized job access for marginalized groups in Indonesia, yet significant challenges remain, including the lack of standard regulations and reliable income mechanisms. Participants cited the flexibility and transparency of platform work, though noted its limitations, such as a dependency on client demand. Platform work offers potential for enhancing Indonesia's digital economy by facilitating flexible employment options in the communication industry. Policymakers could support this emerging workforce with standardized fee structures, protection policies, and collaboration with established firms, fostering sustainable development for platform work in Indonesia’s communication sector.